G protein regulation of neuronal calcium channels: back to the future - Proft, Juliane; Weiss, Norbert (Molecular pharmacology, 2015)
Neuronal voltage-gated calcium channels have evolved as one of the most important players for calcium entry into presynaptic endings responsible for the release of neurotransmitters. In turn, and to fine-tune synaptic activity and neuronal communication, numerous neurotransmitters exert a potent negative feedback over the calcium signal provided by G protein-coupled receptors. This regulation pathway of physiologic importance is also extensively exploited for therapeutic purposes, for instance in the treatment of neuropathic pain by morphine and other μ-opioid receptor agonists. However, despite more than three decades of intensive research, important questions remain unsolved regarding the molecular and cellular mechanisms of direct G protein inhibition of voltage-gated calcium channels. In this study, we revisit this particular regulation and explore new considerations.
Keywords: blokátory kalciových kanálů; Animals; Protein Conformation; GTP-Binding Proteins; neurony; proteiny vázající GTP - gama-podjednotky; presynaptická zakončení; Humans; GTP-Binding Protein gamma Subunits; Neurons; Presynaptic Terminals; proteiny vázající GTP; proteiny vázající GTP - beta-podjednotky; lidé; Calcium Channels; zvířata; receptory spřažené s G-proteiny; Calcium Channel Blockers; Receptors, G-Protein-Coupled; konformace proteinů; vápníkové kanály; GTP-Binding Protein beta Subunits